2021
DOI: 10.21071/az.v70i271.5514
|View full text |Cite
|
Sign up to set email alerts
|

Typologie des systèmes d’élevage caprin en milieu rural au Bénin en vue d’une étude ultérieure de leur durabilité

Abstract: Cette étude a été entreprise afin de caractériser la diversité des systèmes d’élevage caprin et identifier les principales contraintes et opportunités pour leur durabilité dans les différentes zones agro-écologiques du Bénin. Les données collectées sur 478 troupeaux caprins ruraux élevés dans quatre communes du Bénin ont été soumises à une analyse en composantes principales catégorielles et à l’algorithme de classification “two-step” du logiciel statistique IBM®-SPSS®. Quatre différents types d’élevages caprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Improving traditional pastoralism systems is needed as an adaptation and mitigation strategy to be used by smallholder farmers in Benin [10]. Small ruminants are kept on small-scale farms and play an important role in the livelihood strategies of resource-poor farmers [11,12], including income generation, insurance (sale for cash to meet unexpected expenditures), economic Sustainability 2024, 16, 2270 2 of 15 security (sale for cash to support foreseeable expenses), social/religious functions, and prestige in ownership [13]. Sheep rearing is particularly an important activity generating income for farmers due to the animal sale value in extensive production systems in rural areas and in fattening systems around cities [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving traditional pastoralism systems is needed as an adaptation and mitigation strategy to be used by smallholder farmers in Benin [10]. Small ruminants are kept on small-scale farms and play an important role in the livelihood strategies of resource-poor farmers [11,12], including income generation, insurance (sale for cash to meet unexpected expenditures), economic Sustainability 2024, 16, 2270 2 of 15 security (sale for cash to support foreseeable expenses), social/religious functions, and prestige in ownership [13]. Sheep rearing is particularly an important activity generating income for farmers due to the animal sale value in extensive production systems in rural areas and in fattening systems around cities [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated using woody plant leaves as feed in small ruminant farms [15,16]. Their permanent availability over the year and their palatability increase their use [12,[17][18][19]. It has been found that when grasses and other herbaceous forage become scarce on rangelands during the dry season, the quantitative and qualitative imbalance in ruminant rations can be corrected by using one or more woody forage species [20].…”
Section: Introductionmentioning
confidence: 99%
“…Houessou et al (2021) who stated that goat herd size and structure were signi cantly related to AEZ in Benin. The current study has revealed that there is a difference in the average number of goats kept per household between the ZSO (12.93) and the ZSS (15.68).…”
mentioning
confidence: 99%